МЕТОД ПРИНЯТИЯ РЕШЕНИЙ ПО УПРАВЛЕНИЮ СЕТЬЮ С ПОЛУПРОВОДНИКОВЫМИ ПРЕОБРАЗОВАТЕЛЯМИ ЭЛЕКТРОЭНЕРГИИ - Жуйков, В.Я.; Киселев, Г.Д.; Киселева, А.Г. (Інститут електродинаміки НАН України, Київ, 2014)
Managing a network with power semiconductor converters based on object-cognitive approach is described in this article. Using modified triangle foresight approach allows to create rational rules of converters taking into account the context parameters microgrid environment. References 5, figure 1.